Valor prognóstico das proteínas HIF-1α, VEGF e IL-8 em macerado tumoral mamário canino - Ferreira, José Henrique Musumeci (2014)
Introduction: Mammary neoplasms are the most common type of tumor in dogs. Some proteins play an important role in tumor progression, thus are candidate prognosis markers. During tumor growth, the transcription factor induced by hypoxia (HIF-1α) activates the expression of vascular endothelial growth factor (VEGF), promoting angiogenesis. Interleukin-8 (IL-8) is a pro-inflammatory and pro-angiogenic cytokine and has been associated with tumor progression. Objectives: To evaluate the prognostic value of HIF-1α, VEGF and IL-8 proteins in tumor tissue in dogs with mammary tumors, correlating them with clinicopathological parameters, clinical outcome and survival. Material and Methods: The concentrations of HIF-1α, VEGF and IL-8 proteins were evaluated by ELISA (Enzyme-linked immunosorbent) in macerated tumor of 25 bitches with mammary tumors and control samples and compared statistically. Results: The levels of HIF-1α, VEGF and IL-8 were higher in dogs over the age of 10 years and that had died (p <0.05). Moreover, HIF-1α concentrations were elevated in the tumors of dogs who developed metastases (p = 0.04), while VEGF levels were highest in tumors with clinical stages III and IV (p = 0.03) and IL-8 tumors in tumor with development greater than six months (p = 0.03). Still, high levels of HIF-1α, VEGF and IL-8 were also related to shorter overall survival (p <0.05). Conclusions: High levels of HIF-1α, VEGF and IL-8 are associated with features of poor prognosis, suggesting that the assessment of these proteins in tumor macerated has important prognostic value.